Adaptive context-aware pervasive and ubiquitous learning. (5th May 2009) - Economides, Anastasios A.
In pervasive and ubiquitous learning, a learner should be able to freely perform an educational activity possibly cooperating and/or collaborating with others using multiple devices and networks as he moves in an environment. The educational activity should be able to be performed by various types of learners and to operate on various devices, networks and environments. Correspondingly, the devices and the networks should be able to support various types of learners and to operate various educational activities in any environment. In order to provide adaptive context-aware pervasive and ubiquitous learning, an adaptation engine senses the context and produces adapted educational activity and infrastructure. This paper defines the context to consist of the learner state, the educational activity state, the infrastructure state and the environment state. Furthermore, it comprehensively describes each one of the states.